Combat for the stage & screen - Bushey, David; University of Washington. Instructional Media Services Television (Seattle, WA : Instructional Media Services Television, University of Washington, 1985)
Provides the basis for a ten-week training course in combat techniques. Extensive use of slow motion and stop action allows for careful analysis of movement, emphasizing safety techniques and realism. Introduces fight choreography and a practical notation system.
#1. Medieval weaponry -- #2. Elizabethan weaponry -- #3. Unarmed combat.
Title on container: Combat for stage and screen.
Keywords: Stage combat; Stage fencing